ADVERSITY QUOTIENT DITINJAU DARI SELF-EFFICACY PADA SISWA SMP X DI PEKALONGAN - Warhana, Arradhika; Arum Permitasari, I Rheny (IMAGE, 2025)
This study aims to test whether there is a relationship between self-efficacy and adversity quotient in students of SMP X Pekalongan. The hypothesis put forward in this study is "there is a positive relationship between self-ability and adversity quotient in students of SMP X Pekalongan". This study uses two measuring instruments, namely the adversity quotient scale and the self-efficacy scale. The respondents involved in this study were 211 students of grade IX of SMP X Pekalongan. This study uses Spearman-rho non-parametric correlation analysis as a method of testing the research hypothesis. Based on the correlation test, the coefficient result was 0.750 with a significance level of 0.00 or p <0.01. This confirms the existence of a significant positive relationship between self-efficacy and adversity quotient in students of SMP X Pekalongan. Or in other words, the research hypothesis is accepted. In addition, this study also found that the self-efficacy variable made an effective contribution of 58.3% to the adversity quotient variable of students of SMP X Pekalongan. Meanwhile, the remaining 41.7% is influenced by other factors not discussed in this study. Keywords: adversity quotient, self-efficacy